Human-Centric Information Processing Through Granular Modelling - Bargiela, Andrzej (Springer, 2017)
The idea of Human-Centric Information Processing was prompted by the pioneering work of Zadeh Towards a theory of fuzzy information granulation and its centrality in human reasoning and fuzzy logic (1997). Since the publication of this work, a large number of researchers have focused on identifying the nature of information granulation and its specific relationship to human information processing. We now begin to witness the rich and manifold results of this concentrated research effort of the last decade (...)